2019
DOI: 10.3389/fphys.2019.01271
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary Resistance Running as a Model to Induce mTOR Activation in Mouse Skeletal Muscle

Abstract: Long-term voluntary resistance running has been shown to be a valid model to induce muscle growth in rodents. Moreover, the mammalian target of rapamycin complex 1 (mTORC1) is a key signaling complex regulating exercise/nutrient-induced alterations in muscle protein synthesis. How acute resistance running affects mTORC1 signaling in muscle and if resistance applied to the wheel can modulate mTORC1 activation has not yet been fully elucidated. Here, we show that both acute resistance running and acute free runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 45 publications
5
25
0
Order By: Relevance
“…Interestingly, running increased the SC contribution to SOL, PLT and GAS, whereas we did not observe a clear increase in SC contribution to fibers upon exercise in TA, nor EDL ( Figure 2B,C), confirming previous observations from our group that wheel running specifically recruits the hindlimb plantar flexors (D'Hulst et al, 2019).…”
Section: Exercise Promotes Sc Contribution To Myofibers In a Load-depsupporting
confidence: 91%
See 1 more Smart Citation
“…Interestingly, running increased the SC contribution to SOL, PLT and GAS, whereas we did not observe a clear increase in SC contribution to fibers upon exercise in TA, nor EDL ( Figure 2B,C), confirming previous observations from our group that wheel running specifically recruits the hindlimb plantar flexors (D'Hulst et al, 2019).…”
Section: Exercise Promotes Sc Contribution To Myofibers In a Load-depsupporting
confidence: 91%
“…The dorsi flexors undergo much less mechanical load since they only keep the foot up in the swing phase (Carlson-Kuhta et al, 1998). In this respect, recent work from our group has shown that acute VResRun increases mTORC1 signaling exclusively in SOL, PLT and the oxidative part of the GAS, but not in TA (D'Hulst et al, 2019). Moreover, muscle hypertrophy is predominantly observed in plantar flexors upon resistance running, as opposed to dorsi flexors (Call et al, 2010;Konhilas et al, 2005;Legerlotz et al, 2008;White et al, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, in agreement with previous work [9,10], we found that in the nonexercising control mice, 5-20% of all myo bers were GFP + , with the highest contribution of SCs in the SOL, con rming that SC fusion occurs in hindlimb muscles of sedentary mice ( Figure 2B-D). Interestingly, running increased the SC contribution to SOL, PLT and GAS, whereas we did not observe a clear increase in SC contribution to bers upon exercise in TA, nor EDL ( Figure 2B-D), con rming previous observations from our group that wheel running speci cally recruits the hindlimb plantar exors [42]. Moreover, SC contribution to the SOL was load-dependent, as VResRun further increased the number of GFP + myo bers compared to VRun alone, resulting in 80% GFP + myo bers vs. 60% in VRun condition.…”
Section: Exercise Promotes Sc Contribution To Myo Bers In a Load-depesupporting
confidence: 89%
“…The dorsi exors undergo much less mechanical load since they only keep the foot up in the swing phase [45]. In this respect, recent work from our group has shown that acute VResRun increases mTORC1 signaling exclusively in SOL, PLT and the oxidative part of the GAS, but not in TA [42]. Moreover, muscle hypertrophy is predominantly observed in plantar exors upon resistance running, as opposed to dorsi exors [24,34,46].…”
Section: Discussionmentioning
confidence: 99%
“…Physiological resistance 620 training protocols leading to skeletal muscle hypertrophy in mice are difficult to achieve. The 621 protocols, which are available such as voluntary resistance running [85] and high intensity 622 interval running [86] future studies should investigate the potential of longer-term resistance exercise training in 626 alleviation of mTORC1 hyperactivity in (mouse models of) progeria. To be noted though is that 627 the above mentioned exercise regimes were applied already at young (10-12 weeks) up to old 628 age thereby making it unknown whether they would have the same effect in older PolgA mice 629 already displaying signs of aging.…”
mentioning
confidence: 99%